UNLOCKING THE MIND-BODY CONNECTION: BRUXISM VERSUS PSYCHOLOGICAL FACTORS - Mirela Ioana Fluerasu; Ioana Corina Bocsan; Smaranda Buduru; Simona Maria Iacob; Andrea Maria Chisnoiu; Andra Nichimis; Antonela Berar; Marius Negucioiu; Daniela Popa (Romanian Journal of Oral Rehabilitation)
Bruxism is a non-functional activity of the dental-maxillary apparatus characterized by repetitive, unconscious movements, such as grinding or clenching teeth and/or thrusting the mandible. Nowadays, bruxism is no longer considered a disorder or a disease but a behavior that can sometimes have consequences for the structures of the dental-maxillary apparatus.